Cluster-derived rare earth-based composite electromagnetic wave absorbing material and preparation method thereof

By recombining carboxylated multi-wall carbon nanotubes with cluster compound crystals and pyrolyzed high-temperature carbonization, cluster-derived rare earth-based composite electromagnetic wave absorption materials were prepared, which solved the problems of impedance mismatch and complex preparation of traditional absorbing materials, and achieved the Efficient electromagnetic wave absorption performance improves.

CN119277744AActive Publication Date: 2025-01-07XI AN JIAOTONG UNIV
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411403346.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-07
Estimated Expiration
2044-10-09

AI Technical Summary

Technical Problem

The loss mechanism of traditional single-component carbon system and magnetic metal absorbing materials is single, and the impedance is mismatched, resulting in poor absorption performance and complex preparation of rare earth complexes, which limits the application of materials.

Method used

Carboxylated multi-walled carbon nanotubes are used to recombinate with cluster compound crystals, and the clustered compound crystals are prepared by high-temperature pyrolysis carbonization. The dielectric properties of the composite material are strengthened by carbon-based materials and through rare earth metal ions. Electromagnetic characteristics improve magnetic loss performance.

Benefits of technology

The material's wave absorption performance is significantly improved, and the electromagnetic wave absorption effect is achieved, the wave absorption performance is improved by 3 times, and the material's minimum reflection loss and effective absorption bandwidth are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119277744A_ABST
    Figure CN119277744A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of wave absorbing materials, in particular to a cluster-derived rare-earth-based composite electromagnetic wave absorbing material and a preparation method thereof.The rare-earth-based composite electromagnetic wave absorbing material is a compound obtained by compounding carboxylated multi-walled carbon nanotubes and cluster crystals; and calcining the compound at the temperature of 400-700 DEG C to obtain the catalyst. The rare earth-based coordination cluster crystal is used as a precursor and is compounded with the carbon-based material for high-temperature pyrolysis carbonization to prepare the cluster-derived rare earth-based composite electromagnetic wave absorbing material, the dielectric property of the composite material is enhanced by virtue of the carbon-based material, and the magnetic loss performance of the material is greatly improved by virtue of the electromagnetic property of rare earth metal ions; finally, the material has good wave-absorbing performance, the application of rare earth elements in the aspect of wave-absorbing materials is further expanded, and meanwhile the problems that a traditional single-component carbon system / magnetic metal wave-absorbing material is single in loss mechanism and not matched in impedance, and consequently the wave-absorbing performance of the material is poor are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of absorbing materials, and in particular to a cluster-derived rare earth-based composite electromagnetic wave absorbing material and a preparation method thereof. Background Art

[0002] Nowadays, electromagnetic wave technology is widely used. While it brings convenience to people's lives, it also brings serious electromagnetic pollution. Electromagnetic pollution mainly includes electromagnetic radiation and electromagnetic interference, which poses a potential threat to human health and the normal operation of electronic equipment. Wave-absorbing material, referred to as MAM, is a material that can absorb most of the incident electromagnetic waves and minimize the reflection of electromagnetic waves on the surface. This type of material can convert the electromagnetic waves entering the material into a variety of other energies for dissipation and attenuation, avoiding the reflection and transmission of electromagnetic waves as much as possible, thereby reducing electromagnetic pollution and maintaining the stability and safety of electronic equipment. Therefore, the development of high-efficiency electromagnetic wave absorbing materials is a key strategy to effectively reduce electromagnetic pollution.

[0003] At present, researchers have discovered a variety of materials that can be used to prepare absorbing materials, such as carbon materials, magnetic metal materials, semiconductor materials, polymer materials, etc. However, single-component absorbing materials have certain disadvantages and limitations in electromagnetic properties and performance. For conductive loss-type absorbing materials, the problem of too high conductivity greatly limits the application of the material. The existence of the skin effect will lead to enhanced surface reflection of the material and poor impedance matching. For magnetic loss-type materials, the shortcomings of a single component will also limit their practical application. Magnetic loss-type materials generally have a large density, resulting in heavy material mass and not conducive to practical application.

[0004] Rare earth elements, due to their excellent physical properties, such as high magnetic susceptibility, high saturation magnetization and large magnetocrystalline anisotropy, are gradually used in absorbing materials. Studies have shown that doping with rare earth elements can well adjust the impedance matching of materials, making the materials have better electromagnetic wave absorption performance. However, due to the large radius of rare earth ions, high charge, and complex and changeable coordination modes, the preparation of porous rare earth complexes is full of challenges. Summary of the invention

[0005] In order to solve the problem that the traditional single-component carbon-based absorbing materials and magnetic metal absorbing materials have a single loss mechanism and impedance mismatch, resulting in poor absorbing performance of the materials, the purpose of the present invention is to provide a cluster-derived rare earth-based composite electromagnetic wave absorbing material and a preparation method thereof. The method of the present invention provides a theoretical basis for further expanding the application of rare earth elements in absorbing materials.

[0006] To achieve the above objectives, the technical solution of the present invention is as follows.

[0007] The first aspect of the present invention provides a method for preparing a cluster-derived rare earth-based composite electromagnetic wave absorbing material, comprising the following steps:

[0008] The carboxylated multi-walled carbon nanotubes and cluster crystals are compounded to prepare a composite; the mass ratio of the carboxylated multi-walled carbon nanotubes to the cluster crystals is 10 to 20:1; the cluster crystals are {Ni 120 Sm 96}Crystal, {Ni 120 G 96}Crystal, {Ni 120 Nd 96 Any one of the crystals;

[0009] The composite is calcined at 400-700° C. to obtain a cluster-derived rare earth-based composite electromagnetic wave absorbing material.

[0010] Preferably, the crystal parameters of the cluster crystal are: {Ni 120 Nd 96 The crystal parameters of the crystal are: crystallized in the triclinic system, the space group is P-1, and the unit cell parameters are c=

[0011] α=71.29deg, β=66.63deg, γ=77.07deg, {Ni 120 Sm 96}

[0012] The crystal parameters of the crystal are: crystallized in the triclinic system, the space group is P-1, and the unit cell parameters are α=71.15deg, β=66.62deg, γ=77.32deg, {Ni 120 G 96 The crystal parameters of the crystal are: crystallized in the triclinic system, the space group is P-1, and the unit cell parameters are α=71.15deg, β=66.24deg, γ=77.00deg,

[0013] Preferably, the cluster compound crystal is prepared by the following method: nickel salt, rare earth salt, N-methyliminodiacetic acid, potassium bromide and methanol are mixed evenly, and then triethylamine is added to react at 140°C. After the reaction is complete, a cluster compound crystal is prepared; the nickel salt is Ni(CH3COO)2·4H2O; the rare earth salt is any one of Nd(NO3)3·6H2O, Sm(NO3)3·6H2O, and Gd(NO3)3·6H2O. Preferably, the amount ratio of nickel salt, rare earth salt, N-methyliminodiacetic acid, potassium bromide and methanol is 1.2mmol~1.3mmol:1.2mmol~1.3mmol:0.1mmol:0.4mmol~0.5mmol:9mL; the amount ratio of triethylamine to methanol is 9mL:300μL. The corresponding cluster compound crystal can be prepared within this ratio range.

[0014] Preferably, the dimensions of the carboxylated multi-walled carbon nanotubes are: inner diameter 2nm-5nm, outer diameter 5nm-15nm, and length 10μm-30μm.

[0015] Preferably, the specific preparation process of the composite is as follows: ultrasonically dispersing carboxylated multi-walled carbon nanotubes in water to obtain a carboxylated multi-walled carbon nanotube solution; ultrasonically dispersing cluster compound crystals in water to obtain a cluster compound crystal solution; mixing the carboxylated multi-walled carbon nanotube solution and the cluster compound crystal solution, and then continuing ultrasonic treatment. After the ultrasonic treatment is completed, filtering and drying are performed to obtain the composite. Preferably, the ultrasonic treatment is continued for 8 to 12 hours. Preferably, the temperature for the continued ultrasonic treatment is controlled at ≤60°C. Preferably, the calcination time is 2 hours. Preferably, the calcination is carried out under the protection of an inert gas.

[0016] The second aspect of the present invention also provides a cluster-derived rare earth-based composite electromagnetic wave absorbing material prepared by the preparation method described in the first aspect.

[0017] Beneficial effects of the present invention:

[0018] 1. The present invention uses cluster compound crystals as precursors and compounds them with carbon-based materials to perform high-temperature pyrolysis and carbonization to prepare cluster-derived rare earth-based composite electromagnetic wave absorbing materials. While using carbon-based materials to enhance the dielectric properties of the composite materials, the electromagnetic properties of rare earth metal ions are utilized to greatly improve the magnetic loss performance of the material, ultimately making the material have good absorbing performance. This not only further expands the application of rare earth elements in absorbing materials, but also solves the problem of poor absorbing performance of the material due to the single loss mechanism and impedance mismatch of traditional single-component carbon-based / magnetic metal absorbing materials.

[0019] 2. The rare earth-based composite electromagnetic wave absorbing material prepared by the present invention with a mass ratio of 10:1 of carbon-based material and cluster crystals has a minimum reflection loss of -58.85dB at a thickness of 3mm; the rare earth-based composite electromagnetic wave absorbing material prepared with a mass ratio of 15:1 has a minimum reflection loss of -40.04dB at a thickness of 4mm; the rare earth-based composite electromagnetic wave absorbing material prepared with a mass ratio of 20:1 has a minimum reflection loss of -23.79dB; and the effective absorption bandwidth reaches 16.85GHz. Compared with the material performance of the material not composited with the material mentioned above, the wave absorption performance of the material obtained by high-temperature pyrolysis and carbonization of the composite of carbon-based material and cluster crystals in the present invention is improved by 3 times, which is mainly attributed to the increase in carbon content in the material, which leads to an increase in the electrical loss of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The graphs are the wave absorption performance graphs of the samples prepared in Examples 1 to 3. Among them, (a) is the reflection loss graph of Gd / Ni@C-500; (b) is the reflection loss graph of Sm / Ni@C-500; (c) is the reflection loss graph of Nd / Ni@C-500; (d) is the three-dimensional relationship graph of reflection loss of Gd / Ni@C-500, frequency and thickness; (e) is the three-dimensional relationship graph of reflection loss of Sm / Ni@C-500, frequency and thickness; (f) is the three-dimensional relationship graph of reflection loss of Nd / Ni@C-500, frequency and thickness.

[0021] Figure 2 The powder X-ray diffraction patterns of the samples prepared in Examples 3 to 6 are shown in Figure 1. (b) is a partial enlarged view of the dotted line framed portion in (a).

[0022] Figure 3 The SEM images of Sm / Ni@C-500 are shown in Figure 1. (a) is the SEM image before high-temperature carbonization; (b) is the SEM image under low magnification after high-temperature carbonization; (c) is the SEM image under high magnification after high-temperature carbonization; (d) to (i) are TEM images after high-temperature carbonization.

[0023] Figure 4 In the figure, (j) is a high-resolution transmission electron microscopy image of Sm / Ni@C-400; (k) is a high-resolution transmission electron microscopy image of Sm / Ni@C-500.

[0024] Figure 5 The XPS spectra of Sm / Ni@C-700, where (a) is the C1s spectrum, (b) is the O 1s spectrum, (c) is the Sm 3d spectrum, and (d) is the Ni 2p spectrum.

[0025] Figure 6In the figure, (a) is the XPS total spectrum of Sm / Ni@C-500; (b) is the C1s spectrum of Sm / Ni@C-500; (c) is the O1s spectrum of Sm / Ni@C-500; (d) is the Sm 3d spectrum of Sm / Ni@C-500; (e) is the Ni 2p spectrum of Sm / Ni@C-500; (f) is the Raman spectra of Sm / Ni@C-400, Sm / Ni@C-500, Sm / Ni@C-600 and Sm / Ni@C-700.

[0026] Figure 7 The microwave absorption performance diagram of Sm / Ni@C-400, Sm / Ni@C-500, Sm / Ni@C-600, and Sm / Ni@C-700. Among them, (a) is the curve of the real part of the dielectric constant changing with frequency; (b) is the curve of the imaginary part of the dielectric constant changing with frequency; (c) is the curve of the dielectric loss tangent changing with frequency; (d) is the curve of the real part of the magnetic permeability changing with frequency; (e) is the curve of the imaginary part of the magnetic permeability changing with frequency; (f) is the curve of the magnetic loss tangent changing with frequency.

[0027] Figure 8 The reflection loss value of Sm / Ni@C-400 varies with frequency. (a) is a two-dimensional graph; (b) is a three-dimensional graph.

[0028] Fig. 9 The reflection loss value of Sm / Ni@C-500 varies with frequency. (a) is a two-dimensional graph; (b) is a three-dimensional graph.

[0029] Fig.10 The reflection loss value of Sm / Ni@C-600 varies with frequency. (a) is a two-dimensional graph; (b) is a three-dimensional graph.

[0030] Fig.11 The reflection loss value of Sm / Ni@C-700 varies with frequency. (a) is a two-dimensional graph; (b) is a three-dimensional graph.

[0031] Fig.12 This is the transmission electron microscope image of sample SmNi / C@CNTs-10:1.

[0032] Fig.13 The powder X-ray diffraction patterns and Raman spectra of three samples SmNi / C@CNTs-10:1, SmNi / C@CNTs-15:1, and SmNi / C@CNTs-20:1. (a) is the powder X-ray diffraction pattern; (b) is the Raman spectrum.

[0033] Fig.14The diagram is a microwave absorption performance diagram of carboxylated multi-walled carbon nanotubes when the doping ratio is 50%. Among them, (b) is a partial enlarged diagram of part A in (a).

[0034] Fig.15 The microwave absorption performance diagram of SmNi / C@CNTs-10:1, SmNi / C@CNTs-15:1, and SmNi / C@CNTs-20:1. Among them, (a) is the curve of the real part of the dielectric constant changing with frequency; (b) is the curve of the imaginary part of the dielectric constant changing with frequency; (c) is the curve of the dielectric loss tangent changing with frequency; (d) is the curve of the real part of the magnetic permeability changing with frequency; (e) is the curve of the imaginary part of the magnetic permeability changing with frequency; (f) is the curve of the magnetic loss tangent changing with frequency.

[0035] Fig.16 In the figure, (a) is a two-dimensional graph of the reflection loss value of SmNi / C@CNTs-10:1 changing with frequency; (b) is a two-dimensional graph of the reflection loss value of SmNi / C@CNTs-15:1 changing with frequency; (c) is a two-dimensional graph of the reflection loss value of SmNi / C@CNTs-20:1 changing with frequency; (d) is a three-dimensional graph of the reflection loss value of SmNi / C@CNTs-10:1 changing with frequency; (e) is a three-dimensional graph of the reflection loss value of SmNi / C@CNTs-15:1 changing with frequency; (f) is a three-dimensional graph of the reflection loss value of SmNi / C@CNTs-20:1 changing with frequency. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.

[0037] Unless otherwise specified, the methods described in the following examples are all conventional methods; the reagents and materials described are all commercially available unless otherwise specified.

[0038] RL min is the minimum reflection loss. SEM is a scanning electron microscope. TEM is a transmission electron microscope. HRTEM is a high-resolution transmission electron microscope. XPS is an X-ray photoelectron spectroscopy.

[0039] In the following embodiments, carboxylated multi-walled carbon nanotubes were purchased through commercial channels. The product supplier is Shanghai Haohong Biomedical Technology Co., Ltd., the brand is Leyan, the purity is >99%, the inner diameter is 2nm~5nm, the outer diameter is 5nm~15nm, and the length is 10μm~30μm.

[0040] Example 1

[0041] Cluster {Ni 120 Nd 96 A method for preparing a carbon-based composite material comprises the following steps:

[0042] Step 1, {Ni 120 Nd 96 Preparation of {Ni(CH3COO)2·4H2O 1.24mmol, Nd(NO3)3·6H2O 1.24mmol, N-methyliminodiacetic acid 0.10mmol, potassium bromide 0.42mmol were mixed and dissolved in 9mL of pure methanol, and then 300μL of triethylamine was added to adjust the pH of the solution. Finally, the mixed solution was added to a 12mL polyethylene reactor, and the temperature was raised to the target temperature of 140℃ within 1 hour, and kept heated at 140℃ for 72h, and then cooled to room temperature within 36h. After washing with ethanol at room temperature, regular light blue block crystals were obtained, which were recorded as {Ni 120 Nd 96} crystal. Based on Nd calculation, {Ni 120 Nd 96 The yield of crystals was about 60%.

[0043] Step 2, Cluster {Ni 120 Nd 96 Preparation of carbon-based composite materials: Prepared {Ni 120 Nd 96 The crystals were washed with anhydrous ethanol, filtered with filter paper, and placed in a fume hood to air dry naturally. After drying, they were fully ground in a mortar to obtain a powder sample. The obtained powder sample was then loaded into a high-temperature resistant quartz boat and placed in a tubular furnace filled with nitrogen gas. The temperature was heated to 500°C at a heating rate of 5°C / min and continued for 2 hours, then cooled naturally to room temperature. The cluster compound {Ni 120 Nd 96}Carbon-based composite material, denoted as Nd / Ni@C-500, has a product yield of about 50%.

[0044] Example 2

[0045] Cluster {Ni 120 G 96 A method for preparing a carbon-based composite material comprises the following steps:

[0046] Step 1, {Ni 120 G 96Preparation of {Ni(CH3COO)2·4H2O 1.24mmol, Gd(NO3)3·6H2O 1.24mmol, N-methyliminodiacetic acid 0.10mmol, bromide 0.42mmol were mixed and dissolved in 9mL of pure methanol, and then 300μL of triethylamine was added to adjust the pH of the solution. Finally, the mixed solution was added to a 12mL polyethylene reactor, and the temperature was raised to the target temperature of 140℃ within 1 hour, and kept heated at 140℃ for 72h, and then cooled to room temperature within 36h. After washing with ethanol at room temperature, regular light blue block crystals were obtained, which were recorded as {Ni 120 G 96} crystal, calculated based on Gd, {Ni 120 G 96 The yield of crystals was about 60%.

[0047] Step 2, Cluster {Ni 120 G 96 Preparation of carbon-based composite materials: Prepared {Ni 120 G 96 The crystals were washed with anhydrous ethanol, filtered with filter paper, and placed in a fume hood to air dry naturally. After drying, they were fully ground in a mortar to obtain a powder sample. The obtained powder sample was then loaded into a high-temperature resistant quartz boat and placed in a tubular furnace filled with nitrogen gas. The temperature was heated to 500°C at a heating rate of 5°C / min and continued for 2 hours, then cooled naturally to room temperature. The cluster compound {Ni 120 G 96}Carbon-based composite material, denoted as Gd / Ni@C-500, has a product yield of about 50%.

[0048] Example 3

[0049] Cluster {Ni 120 Sm 96 A method for preparing a carbon-based composite material comprises the following steps:

[0050] Step 1, {Ni 120 Sm 96Preparation of {Ni(CH3COO)2·4H2O 1.24mmol, Sm(NO3)3·6H2O 1.24mmol, N-methyliminodiacetic acid 0.10mmol, potassium bromide 0.42mmol were mixed and dissolved in 9mL of pure methanol, and then 300μL of triethylamine (about 2.14mmol) was added to adjust the pH of the solution. Finally, the mixed solution was added to a 12mL polyethylene reactor, and the temperature was raised to the target temperature of 140℃ within 1 hour, and kept heated at 140℃ for 72h, and then cooled to room temperature within 36h. After washing with ethanol at room temperature, regular light blue block crystals were obtained, which were recorded as {Ni 120 Sm 96} crystal, calculated based on Sm, {Ni 120 Sm 96 The yield of crystals was about 60%.

[0051] Step 2, Cluster {Ni 120 Sm 96 Preparation of carbon-based composite materials: Prepared {Ni 120 Sm 96 The crystals were washed with anhydrous ethanol, filtered with filter paper, and placed in a fume hood to air dry naturally. After drying, they were fully ground in a mortar to obtain a powder sample. The obtained powder sample was then loaded into a high-temperature resistant quartz boat and placed in a tubular furnace filled with nitrogen gas. The temperature was heated to 500°C at a heating rate of 5°C / min and continued for 2 hours, then cooled naturally to room temperature. The cluster compound {Ni 120 Sm 96}Carbon-based composite material, denoted as Sm / Ni@C-500, has a product yield of about 52%.

[0052] In order to explore the suitable experimental conditions for preparing microwave absorbing materials using different clusters as self-sacrificial templates, {Ni 120 Nd 96}、{Ni 120 G 96}、{Ni 120 Sm 96 Three crystals were used as precursors. Three samples were initially obtained at an experimental temperature of 500°C: Nd / Ni@C-500, Gd / Ni@C-500, and Sm / Ni@C-500. The microwave absorption properties of the three samples were investigated. The results are shown in Figure 2. Figure 1 shown.

[0053] from Figure 1It can be seen that when the thickness is 7mm, the minimum reflection loss of Gd / Ni@C-500, Sm / Ni@C-500, and Nd / Ni@C-500 can reach -39.59dB, -40.65dB, and -21.85dB, respectively. Compared with the reported absorbing materials, the RL of the three is min The reflection loss absorption of Sm / Ni@C-500 and Gd / Ni@C-500 is close and strong, but the overall effective absorption frequency range of Gd / Ni@C-500 is the lowest. Therefore, through preliminary research, it is found that among the three different rare earth samples, {Ni 120 Sm 96} is the best precursor for preparing carbon-based composite materials, so {Ni 120 Sm 96}Crystals are used as precursors for subsequent experiments to further explore the effects of factors such as temperature on material properties. It should be noted that due to the high magnetic metal content of the three samples prepared in Examples 1 to 3 and the low carbon content of electrical losses, the effective absorption frequency range of the three samples is relatively narrow, approximately 2 GHz, and is only distributed in the second half of the frequency range. This is because magnetic losses are enhanced under high-frequency conditions. In addition, when testing samples using a vector network analyzer, the samples are required to be mixed with a paraffin matrix in a certain proportion before testing. Here, the doping ratio of all samples is 70%. Obviously, this is a relatively high ratio. Therefore, a key to subsequent testing is to reduce the doping ratio of the samples from 70% to 50% for experimental exploration.

[0054] Example 4

[0055] Cluster {Ni 120 Sm 96 The method for preparing the carbon-based composite material is different from that of Example 3 in that the temperature is heated to 400°C at a heating rate of 5°C / min and continued to be heated for 2 hours, and then cooled naturally to room temperature. 120 Sm 96}Carbon-based composite material, denoted as Sm / Ni@C-400, has a product yield of about 55%.

[0056] Example 5

[0057] Cluster {Ni 120 Sm 96 The method for preparing the carbon-based composite material is different from that of Example 3 in that the temperature is increased to 600°C at a rate of 5°C / min and continued for 2 hours, and then cooled naturally to room temperature. 120 Sm 96}Carbon-based composite material, denoted as Sm / Ni@C-600, has a product yield of about 50%.

[0058] Example 6

[0059] Cluster {Ni 120 Sm 96 The method for preparing the carbon-based composite material is different from that of Example 3 in that the temperature is increased to 700°C at a rate of 5°C / min and continued for 2 hours, and then cooled naturally to room temperature. 120 Sm 96}Carbon-based composite material, denoted as Sm / Ni@C-700, has a product yield of about 48%.

[0060] Powder X-ray diffraction analysis: {Ni 120 Sm 96 The carbon-based composite materials were prepared by high-temperature carbonization at different temperatures using} crystals as precursors: Sm / Ni@C-400, Sm / Ni@C-500, Sm / Ni@C-600, and Sm / Ni@C-700. The four samples were characterized by powder X-ray diffractometer for phase and structure analysis. The results are shown in Figure 2. Figure 2 shown.

[0061] Compared with the powder diffraction peaks of the precursor, the phase composition of the cluster crystals changed after high-temperature carbonization, and the samples obtained at different calcination temperatures had similar spectra. Figure 2 It can be seen that Sm / Ni@C-700 has obvious and sharp diffraction peaks. The strong diffraction peaks at 44.5°, 51.8° and 76.4° correspond to the diffraction peaks of metallic nickel, PDF#04-0850; they correspond to the (111), (200) and (220) crystal planes of face-centered cubic nickel respectively; four strong diffraction peaks appear at 28.42°, 32.92°, 47.04° and 58.53°, which correspond to the diffraction peaks of Sm2O3, PDF#42-1461 respectively; this proves the presence of pure metallic Ni and rare earth oxide Sm2O3 in the sample.

[0062] For the three samples Sm / Ni@C-400, Sm / Ni@C-500, and Sm / Ni@C-600, the spectra of the three samples show two steamed bun peaks, which may be due to the poor crystallinity of the three samples. Figure 2 It can be seen that as the experimental temperature increases, the peak intensity continues to increase, and each diffraction peak gradually becomes sharper, indicating that the crystallinity of the sample is constantly improving. In addition, no diffraction peak of carbon material was observed in the powder X-ray diffraction spectrum. This may be because the metal content in the four samples is high, while the carbon content is low. The Raman spectrum and X-ray photoelectron spectroscopy can be combined to further analyze the composition of the samples.

[0063] Scanning electron microscopy and transmission electron microscopy analysis: In order to observe the microscopic morphology of the sample, the morphological changes of the sample Sm / Ni@C-500 were characterized by scanning electron microscopy and transmission electron microscopy, such as Figure 3 and Figure 4 shown.

[0064] like Figure 3 , cluster {Ni 120 Sm 96 Before high-temperature carbonization, it was in a regular block shape with a smooth surface. The morphology of the carbonized sample Sm / Ni@C-500 was in the shape of a "small flower", with relatively uniform particles and a rough and wrinkled surface, indicating that the skeleton of the precursor had collapsed during the high-temperature pyrolysis process. Figure 3 Figures (d) to (i) show that the samples after high-temperature carbonization have a loose structure, and Figure (f) shows that the samples may have agglomerated during the calcination process. The dark black and gray parts represent the metal components and the carbon components after carbonization, respectively.

[0065] In order to further obtain the specific composition of samples Sm / Ni@C-400, Sm / Ni@C-500, and Sm / Ni@C-600, the local crystal plane spacing of the lattice fringes in the high-resolution transmission electron microscope images of Sm / Ni@C-400 and Sm / Ni@C-500 samples was analyzed and calculated to assist in determining the composition structure of the material. Figure 4 In the high-resolution transmission electron micrographs of the two samples, lattice fringes of metal Ni and NiO can be observed, which further indicates that in addition to the presence of pure metal Ni, there are other oxides or other Ni-containing compounds in the samples. However, no stripe regions of metal Sm compounds were observed in the electron microscope images, which may be because the experimental temperature was not high enough and the material had not yet formed regular lattice fringes, or because there was no distribution of metal Sm in the selected area.

[0066] X-ray photoelectron spectroscopy analysis: X-ray photoelectron spectroscopy was performed on the sample Sm / Ni@C-700. X-ray photoelectron spectroscopy is referred to as XPS. Peaks of four elements, C, O, Sm, and Ni, can be observed in the XPS total spectrum of the sample Sm / Ni@C-700, proving the existence of the four elements in the sample. The peak position of other spectra was corrected and processed using the C1s peak with a binding energy of 284.8eV. The chemical state of each element in the sample Sm / Ni@C-700 was determined by the position of the peaks corresponding to different binding energies in the element spectrum. Figure 5In the C1s spectrum, the peaks at binding energies of 284.41eV, 286.44eV, and 289eV correspond to CC / C=C, polar groups CO, and C=O bonds, respectively. These polar groups are also the source of polarization resonance in the sample. In the O1s spectrum, the peaks at binding energies of 532.60eV and 531eV correspond to CO and C=O bonds, respectively; and the peak at 529.60eV corresponds to the metal oxide Sm-O bond, which indicates that there are oxides and compounds of Sm in the sample Sm / Ni@C-700. In the Sm3d spectrum, there are two peaks at binding energies of 1084eV and 1110.22eV, which correspond to Sm 3+ Sm 3d 5 / 2 and Sm 3d 3 / 2 orbital, which is consistent with the result of powder X-ray diffraction that Sm2O3 exists. Finally, in the Ni 2p spectrum, the two peaks with binding energies of 854.50 eV and 855.81 eV correspond to the 2p 3 / 2 orbital, while the peak at 871 eV corresponds to the 2p 1 / 2 orbit; in addition, there are two satellite peaks at two positions with binding energies of about 860eV and 880eV. This result shows that in addition to Sm2O3 and elemental metal Ni, the sample Sm / Ni@C-700 may also contain Ni oxides or other metal compounds, which is basically consistent with the results of the powder X-ray diffraction test. Some components are not reflected in the powder X-ray diffraction pattern due to their low content.

[0067] To further confirm the composition of the sample surface and the valence state of the metal elements, the sample Sm / Ni@C-500 was subjected to XPS test. XPS is X-ray photoelectron spectroscopy. Figure 6 As shown in the figure, the appearance of the corresponding peaks of the four elements C, O, Ni, and Sm in the XPS total spectrum proves the existence of these four elements in the sample Sm / Ni@C-500. Similarly, the peak position of other spectra is corrected by the C1s peak with a binding energy of 284.80eV, and the chemical state of each element is determined by the position of the corresponding peaks of different binding energies in the element spectrum. Figure 6 , the spectra of the four elements C, O, Ni, and Sm are separated. In the C1s spectrum, the three peaks corresponding to the binding energies of 284.56eV, 286.21eV, and 289.43eV correspond to CC / C=C, polar group CO, and C=O bonds, respectively. In the O1s spectrum, the two peaks with binding energies of 532.83eV and 531.40eV correspond to CO and C=O bonds, respectively, while the peak at 529.25eV corresponds to the metal oxide bond Sm-O. In the Sm 3d spectrum, there are two peaks with binding energies of 1083.82eV and 1109.41eV, corresponding to the rare earth ion Sm3+ Sm 3d 5 / 2 and Sm 3d 3 / 2 orbital, which is consistent with the presence of Sm2O3 in the phase results of powder X-ray diffraction. Finally, in the Ni 2p spectrum, the three peaks with binding energies of 854eV, 855.60eV, and 856.71eV correspond to the 2p 3 / 2 orbital, the peaks at 871.21eV, 875eV, and 872.61eV correspond to the 2p 1 / 2 orbit. In addition, there are two satellite peaks at two positions with binding energies of approximately 860eV and 880eV. Combined with the results of powder X-ray diffraction, it can be shown that in addition to the presence of elemental metal Ni, the sample Sm / Ni@C-500 also contains Ni oxides or other metal compounds, which may not be reflected in the powder spectrum due to their low content. This is also consistent with the phenomenon that the precursor has low crystallinity at low temperatures and gradually has obvious peaks as the temperature rises to 700°C. Comparing the results of Sm / Ni@C-500 and Sm / Ni@C-700, the types of components of the two are approximately the same, but may differ in content.

[0068] Raman spectroscopy analysis: Raman testing can detect the degree of graphitization of materials. Figure 6 Figure (f) shows that all samples have a peak at 1356 cm -1 and 1610cm -1 There are two obvious bands at two locations, namely D band and G band. G band represents graphite carbon or ordered carbon, and D band represents defects or disordered carbon. The ratio of the two intensities is I G / I D It is a physical quantity for evaluating the degree of graphitization of materials. The larger the ratio, the higher the degree of graphitization of the sample. After calculation, it is found that the I G / I D The values ​​are 0.99, 1.04, 1.07 and 1.09 respectively. This shows that the higher the calcination temperature, the more orderly the arrangement of carbon atoms and the higher the degree of graphitization of the material; accordingly, the conductivity of the sample will also increase, which is conducive to the improvement of the conductivity loss in the sample and will affect the dielectric constant of the material. In addition, the I G / I DThe values ​​are all small, indicating that their degree of graphitization is not high, which is consistent with the fact that there is no obvious carbon peak in the powder X-ray diffraction spectrum. Therefore, the conductivity of the sample is also low, which is consistent with the electromagnetic parameter data measured by subsequent samples. According to the theoretical law of impedance matching of electromagnetic wave absorbing materials, a unilateral increase in conductivity is not conducive to the impedance matching of the material, so a single increase in conductivity does not necessarily make the material have good performance. This is also the reason why the sample Sm / Ni@C-700 has the highest carbon content and dielectric loss, but the performance is not the best. In summary, it can be concluded that the sample Sm / Ni@C-500 is composed of Sm2O3, metal Ni and its metal oxide and carbon complexes. Due to its poor crystallinity, it does not show obvious diffraction peaks in the powder X-ray diffraction spectrum.

[0069] Analysis of electromagnetic wave absorption performance: The real part of the dielectric constant, denoted as ε', represents the material's ability to store external electric field energy; the imaginary part of the dielectric constant, denoted as ε", represents the corresponding loss capacity. The real part of the magnetic permeability, denoted as μ', represents the material's ability to store external magnetic field energy; the imaginary part of the magnetic permeability, denoted as μ", represents the loss capacity of the external magnetic field. The tangent value of the dielectric constant is denoted as tanδε; the tangent value of the magnetic permeability is denoted as tanδμ. The size of tanδε and tanδμ can reflect the loss capacity of the material. Generally speaking, tanδε is positively correlated with the ε" of the material, and the size of tanδμ is positively correlated with the μ" of the material. The larger the values ​​of these two imaginary parts, the stronger the loss capacity of the material.

[0070] Depend on Figure 7 It shows that the ε' of the four samples tends to increase slightly with the increase of frequency, while ε" decreases with the decrease of frequency. Several multiple resonance peaks appear in the curves of the change of ε' and ε" versus frequency, indicating the occurrence of polarization resonance in the samples, which corresponds to the polarization loss in the loss mechanism of the absorbing material, among which the resonance in the high-frequency and low-frequency regions can be attributed to the interface polarization and dipole polarization, respectively. In addition, the values ​​of ε' and ε" increase with the increase of temperature, indicating that a higher calcination temperature can make the material have a larger dielectric loss capacity, which is consistent with the change of tanδε value with temperature, which may be because the higher the temperature, the higher the degree of carbonization. Among them, Sm / Ni@C-700 has the largest tanδε value, indicating that its dielectric loss capacity is the largest. Similarly, the real part μ' and the imaginary part μ" of the magnetic susceptibility of the material both show a slightly downward trend, and the values ​​of both increase with the increase of temperature. This phenomenon shows that the calcination temperature also affects the magnetic properties of the material, which is also consistent with the phase change of the metal elements of the material. The magnetic permeability tangent value tanδμ of the four samples is slightly higher than the dielectric constant tangent value tanδε, indicating that magnetic loss slightly dominates the entire loss attenuation process.

[0071] In order to study the electromagnetic wave absorption performance of four samples Sm / Ni@C-400, Sm / Ni@C-500, Sm / Ni@C-600, Sm / Ni@C-700, the two-dimensional and three-dimensional graphs of the reflection loss value of the four samples Sm / Ni@C-400, Sm / Ni@C-500, Sm / Ni@C-600, Sm / Ni@C-700 as a function of frequency are shown in Figure 2. Figure 8 to Figure 11 As shown. Figure 8 to Figure 11 The results show that the two samples Sm / Ni@C-400 and Sm / Ni@C-700 have almost no wave absorption effect; while the two samples Sm / Ni@C-500 and Sm / Ni@C-600 have a certain wave absorption effect, but the overall performance is not ideal. Under the conditions of a frequency of 15.2GHz and a matching thickness of 8mm, the minimum reflection loss values ​​of the two samples Sm / Ni@C-500 and Sm / Ni@C-600 are -14.09dB and -11.90dB respectively, and the maximum effective absorption frequency bands are both around 2GHz, and are all distributed in the high-frequency region. It can be inferred that the magnetic loss effect of the four samples is stronger because high frequency will enhance the magnetic loss effect.

[0072] According to the above analysis, the absorption performance of the four samples is not ideal, which may be due to the precursor {Ni 120 Sm 96 The magnetic metal content in the structure is too high, while the carbon content is low and the dielectric constant is low, resulting in unbalanced impedance matching. In addition, between 400℃ and 700℃, the performance of the sample shows a trend of first rising and then falling. At 500℃, the wave absorption performance of the sample reaches the best. Further in-depth analysis shows that the various electromagnetic parameters of the sample Sm / Ni@C-500 are not the best, but it has the best performance. This may be because its electromagnetic parameters just achieve a good balance. Therefore, 500℃ was selected as the calcination temperature for subsequent exploratory experiments to carry out the next step of performance optimization experiments.

[0073] Example 7

[0074] {Ni 120 RE 96 A method for preparing a CNTs-derived carbon-based composite material comprises the following steps:

[0075] Step 1, {Ni 120 Sm 96}Crystal preparation: The preparation process is the same as that in Example 3.

[0076] Step 2, {Ni 120 RE 96Preparation of carbon-based composite materials derived from {Ni} / CNTs: Carboxylated multi-walled carbon nanotubes were ultrasonically dispersed in 10 mL of deionized water to obtain a carboxylated multi-walled carbon nanotube solution; 120 Sm 96} crystals were ultrasonically dispersed in 10 mL of deionized water to obtain {Ni 120 Sm 96} solution.

[0077] The carboxylated multi-walled carbon nanotube solution and {Ni 120 Sm 96} solution was mixed and ultrasonicated for 10 h; wherein, carboxyl multi-walled carbon nanotubes and {Ni 120 Sm 96 The mass ratio of {Ni} crystals is 10:1. In order to avoid the influence of water temperature rise on the experiment during the ultrasonic process, cold water should be replaced intermittently. The obtained mixture was centrifuged and washed three times, and the obtained precipitate was placed in a vacuum drying oven and vacuum dried at 60°C for 24 hours. The dried sample was loaded into a high-temperature resistant quartz boat, and then placed in a tubular furnace with nitrogen gas, and heated to 500°C at a heating rate of 5°C / min. After heating for 2 hours, it was naturally cooled to room temperature. Obtained {Ni 120 RE 96} / CNTs derived carbon-based composite materials, denoted as SmNi / C@CNTs-10:1.

[0078] Example 8

[0079] {Ni 120 RE 96 A method for preparing a CNTs-derived carbon-based composite material comprises the following steps:

[0080] Step 1, {Ni 120 Sm 96}Crystal preparation: The preparation process is the same as that in Example 3.

[0081] Step 2, {Ni 120 RE 96 Preparation of carbon-based composite materials derived from CNTs: The difference from Example 7 is that carboxylation of multi-walled carbon nanotubes and {Ni 120 Sm 96 The mass ratio of the crystals is 15:1. 120 RE 96} / CNTs derived carbon-based composite materials, denoted as SmNi / C@CNTs-15:1.

[0082] Example 9

[0083] {Ni 120 RE 96A method for preparing a CNTs-derived carbon-based composite material comprises the following steps:

[0084] Step 1, {Ni 120 Sm 96}Crystal preparation: The preparation process is the same as that in Example 3.

[0085] Step 2, {Ni 120 RE 96 Preparation of carbon-based composite materials derived from CNTs: The difference from Example 7 is that, in which the carboxylated multi-walled carbon nanotubes and {Ni 120 Sm 96 The mass ratio of {Ni} crystals is 20:1. In order to avoid the influence of water temperature rise on the experiment during the ultrasonic process, cold water should be replaced intermittently. The obtained mixture was centrifuged and washed three times, and the obtained precipitate was placed in a vacuum drying oven and vacuum dried at 60°C for 24 hours. The dried sample was loaded into a high-temperature resistant quartz boat, and then placed in a tubular furnace with nitrogen gas, and heated to 500°C at a heating rate of 5°C / min. After heating for 2 hours, it was naturally cooled to room temperature. Obtained {Ni 120 RE 96} / CNTs derived carbon-based composite materials, denoted as SmNi / C@CNTs-20:1.

[0086] High-resolution transmission electron microscopy analysis: In order to verify whether the cluster precursor and carbon nanotubes are successfully composited, high-resolution transmission electron microscopy is used for characterization, such as Fig.12 As shown. It can be seen that the two were successfully composited, and this composite method mainly relies on the electrostatic interaction between ions.

[0087] Powder X-ray diffraction analysis: Powder X-ray diffraction analysis was performed on three samples, SmNi / C@CNTs-10:1, SmNi / C@CNTs-15:1, and SmNi / C@CNTs-20:1, to characterize the phase composition and structure of the three samples, such as Fig.13 As shown in Figure (a). The diffraction peak positions of the three samples are basically the same, with two bun peaks appearing at around 30° and 45°, and the peak intensities are slightly different. Since the carbonization temperature is 500°C, the spectra of the three samples show the same diffraction peaks as Sm / Ni@C-500.

[0088] Laser Raman spectroscopy analysis: Laser Raman spectroscopy was performed on three samples, SmNi / C@CNTs-10:1, SmNi / C@CNTs-15:1, and SmNi / C@CNTs-20:1, to characterize the degree of graphitization of the samples. Fig.13 As shown in Figure (b). At 1356cm -1 and 1610cm -1There are two obvious bands at two locations, with a ratio of I G / I D The ratio of the mass of the cluster precursor to the mass of the carbon nanotubes increases because the higher the content of the carbon nanotubes in the sample, the more ordered graphite carbon there is in the sample. In addition, the graphitization degree of the three samples is not high, which is also consistent with the low content of the composite carbon material in the sample.

[0089] Analysis of electromagnetic wave absorption performance: The wave absorption performance of carboxylated multi-walled carbon nanotubes was tested when the doping ratio was 50%. MWCNTS-COOH is carboxylated multi-walled carbon nanotubes, such as Fig.14 As shown, a single carboxylated carbon nanotube does not exhibit the property of absorbing electromagnetic waves, and does not change with the matching thickness.

[0090] In order to study the microwave absorption performance of the composite material prepared by combining cluster compound 5 with carbon nanotubes, the electromagnetic parameter data curves in the frequency range of 2GH~18GHz were also obtained, as shown in FIG. Fig.15 As shown. The results show that compared with the materials without carbon nanotubes, the ε' and ε" values ​​of the three samples after carbon nanotubes are greatly improved, among which SmNi / C@CNTs-10:1 has the largest ε' and ε" values. The maximum value of ε' changes from 4.65 to 13, and the maximum value of ε" changes from 1.8 to 3.6, which indicates that the dielectric loss of the material has also increased. In addition, the tanδε value of SmNi / C@CNTs-10:1 is also the largest, because it has the highest carbon content, which also shows that when the temperature is the same, the carbon content of the material directly affects its electrical loss. Similarly, there are many strong multiple resonance peaks in the graph of ε' and ε" versus frequency, indicating the existence of polarization resonance. Compared with the uncompounded derivative carbon-based materials, it is found that the polarization resonance intensity of the material after carbon nanotubes is greater than that of the uncompounded derivative materials, the polarization loss of the material is improved, and the performance of the material is enhanced. Compared with the uncompounded carbon-based materials, it is not difficult to find that the μ' and μ" values ​​of the three composite samples have not changed much, and the tangent value tanδμ is still slightly higher than the tanδε value, which indicates that in the entire loss attenuation process of the sample, the effect of magnetic loss is still slightly greater than that of dielectric loss.

[0091] The microwave absorption performance of SmNi / C@CNTs-10∶1, SmNi / C@CNTs-15∶1, and SmNi / C@CNTs-20∶1 was tested. Fig.16As shown. The results show that all three samples have certain absorbing properties, and the properties have been greatly improved compared to the uncomposite materials. Among them, the minimum reflection loss of SmNi / C@CNTs-10∶1 at a thickness of 3mm reaches -58.85dB. The minimum reflection loss of SmNi / C@CNTs-15∶1 at a thickness of 4mm is -40.04dB, and the corresponding effective absorption bandwidth is 14.27GHz. The minimum reflection loss value of SmNi / C@CNTs-20∶1 is -23.79dB, and the effective absorption bandwidth reaches 16.85GHz. In the frequency range of 2GHz to 18GHz, not only the matching thickness of the absorbing material is reduced, the minimum reflection loss value is increased, but also the effective absorption bandwidth is greatly improved.

[0092] Table 1 Performance comparison of samples with a loading ratio of 50wt%

[0093] sample <![CDATA[RL min / dB]]> fm / GHz <![CDATA[d1 / mm]]> <![CDATA[d2 / mm]]> Absorption bandwidth / GHz References ZnO / N-doped C -39.7 8.5 4.0 4.0 4.3 1 <![CDATA[ZrO2 / C]]> -58.7 16.8 1.5 1.7 5.5 2 CuO / C -57.5 14.9 1.6 1.6 4.7 3 <![CDATA[CoS2N-CNTs]]> -65.0 16.4 1.6 1.6 4.2 4 waxberry-like Ni / C -73.2 12.3 2.2 1.8 4.8 5 <![CDATA[Co@NPC@TiO2]]> -51.7 13.8 1.7 5.0 3.0 6 <![CDATA[Co / C@V2O3]]> -40.1 15.2 1.5 1.5 4.6 7 <![CDATA[Co / ZrO2 / C]]> -57.2 15.8 3.3 4.6 6.9 8 <![CDATA[CoFe@C@MnO2]]> -64.0 15.6 1.3 1.6 9.2 9 SmNi / C@CNTs-10:1 -58.9 7.4 3.0 2.0 4.1 Example 7 SmNi / C@CNTs-15:1 -40.1 5.8 4.0 2.0 3.8 Example 8

[0094] Note: RL min is the minimum reflection loss; f m is the matching frequency; d1 is the thickness corresponding to the minimum reflection loss; d2 is the thickness corresponding to the maximum absorption bandwidth.

[0095] Reference 1: Wu QL, JinhH, Chen Wei, et al. Graphitized nitrogen-doped porous carbon composites derived from ZIF-8 as efficient microwave absorption materials[J]. Materials Research Express, 2018, 3(6):065602. Reference 2: Zhang X, Qiao J, Liu C, et al. A MOF-derived ZrO2 / C nanocomposite for efficient electromagnetic wave absorption[J]. Inorganic Chemistry Frontiers, 2020, 7(2):385-393. Reference 3: Ma JN, Zhang XM, Liu W, et al. Direct synthesis of MOF-derived nanoporous CuO / carbon composites for high impedance matching and advanced microwave absorption[J]. Journal of Materials Chemistry C, 2016, 4(48):11419-11426. Reference 4: Yan J, huang Y, han XP, et al. Metal organic framework (ZIF-67)-derived hollow CoS2 / N-doped carbon nanotube composites for extraordinary electromagnetic wave absorption[J]. Composites Part B: Engineering, 2019, 163:67-76. Reference 5: Liu DW, Du YC, X P, et al. Waxberry-like hierarchical Ni@C microspheres with high-performance microwave absorption[J]. Journal of Materials Chemistry C, 2019, 7(17):5037-5046. Reference 6: Zhang XM, Ji GB, Liu W, etal.A novel Co / TiO2nanocomposite derived from a metal-organic framework:synthesis and efficient microwave absorption[J].Journal of MaterialsChemistry C,2019,4(9):1860-1870. Reference 7: Zhou CH,WC,Liu D,et al.Metal-Organic framework derivedhierarchical Co / C@V2O3hollow spheres as a thin,lightweight,andhigh-efficiency electromagnetic wave absorber[J]. Chemistry-AEuropean Journal, 2019, 25(9):2234-2241. Reference 8: Zhang Materials&Interfaces, 2019, 11(39): 35959-35968. Reference 9: Zhang Y, Yang ZH, Li M, etal. heterostructured CoFe@C@MnO2nanocubes for efficient microwave absorption[J]. Chemical Engineering Journal, 2020, 382: 123039.

[0096] The SmNi / C@CNTs-10:1 and SmNi / C@CNTs-15:1 prepared in the embodiments of the present invention have excellent wave absorption performance, and the matching thickness and absorption bandwidth need to be further optimized and improved. This shows that the combination of cluster compounds and carbon nanotubes effectively improves the performance of the material, and also verifies the electromagnetic imbalance problem of the material caused by the high magnetic metal content and low carbon content of cluster-derived carbon-based materials. It fully shows that the combination of magnetic metal particles and oxides with carbon materials can achieve electromagnetic synergy of the material, thereby obtaining an electromagnetic wave absorption material with excellent performance.

[0097] The above results show that rare earth elements can improve the wave absorption performance of materials by affecting the resistivity, grain size and other factors of the materials. 120 RE 96} as a precursor, and a carbon-based composite material was prepared by high-temperature pyrolysis and carbonization. Then multi-walled carbon nanotubes and clusters were compounded in different mass ratios and then carbonized at 500°C. The results show that when the mass ratio of the two is 10:1, the minimum reflection loss RL of the composite material at a thickness of 3 mm is min Reaching -58.85dB, when the mass ratio is 15:1, the minimum reflection loss RL when the material thickness is 4mm min Reach -40.04dB; when the mass ratio is 20:1, the minimum reflection loss RL min The effective absorption bandwidth of the composite material reaches -23.79dB, and the absorption performance of the composite material is improved by 3 times compared with that of the uncomposite material, which is mainly attributed to the increase in the carbon content in the material, which leads to the increase in the electrical loss of the material.

[0098] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a cluster-derived rare earth-based composite electromagnetic wave absorbing material, characterized in that: The following steps are involved: The carboxylated multi-walled carbon nanotubes and cluster crystals are compounded to prepare a composite; the mass ratio of the carboxylated multi-walled carbon nanotubes to the cluster crystals is 10 to 20:1; the cluster crystals are {Ni 120 Sm 96 }Crystal, {Ni 120 G 96 }Crystal, {Ni 120 Nd 96 Any one of the crystals; The composite is calcined at 400-700 DEG C to obtain a cluster-derived rare earth-based composite electromagnetic wave absorbing material.

2. The method for preparing the cluster-derived rare earth-based composite electromagnetic wave absorbing material according to claim 1, characterized in that: The crystal parameters of the cluster compound crystal are: {Ni 120 Nd 96 The crystal parameters of the crystal are: crystallized in the triclinic system, the space group is P-1, and the unit cell parameters are α=71.29deg, β=66.63deg, γ=77.07deg, {Ni 120 Sm 96 The crystal parameters of the crystal are: crystallized in the triclinic system, the space group is P-1, and the unit cell parameters are α=71.15deg, β=66.62deg, γ=77.32deg, {Ni 120 G 96 The crystal parameters of the crystal are: crystallized in the triclinic system, the space group is P-1, and the unit cell parameters are α=71.15deg, β=66.24deg, γ=77.00deg, 3. The method for preparing the cluster-derived rare earth-based composite electromagnetic wave absorbing material according to claim 1, characterized in that: The cluster compound crystal is prepared by the following method: Nickel salt, rare earth salt, N-methyliminodiacetic acid, potassium bromide and methanol are uniformly mixed, and then triethylamine is added to react at 140° C. After the reaction is complete, cluster compound crystals are prepared; The nickel salt is Ni(CH3COO)2·4H2O; the rare earth salt is any one of Nd(NO3)3·6H2O, Sm(NO3)3·6H2O, and Gd(NO3)3·6H2O.

4. The method for preparing the cluster-derived rare earth-based composite electromagnetic wave absorbing material according to claim 2, characterized in that: The usage ratio of nickel salt, rare earth salt, N-methyliminodiacetic acid, potassium bromide and methanol is 1.2mmol~1.3mmol:1.2mmol~1.3mmol:0.1mmol:0.4mmol~0.5mmol:9mL; the usage ratio of triethylamine and methanol is 9mL:300μL.

5. The method for preparing the cluster-derived rare earth-based composite electromagnetic wave absorbing material according to claim 1, characterized in that: The dimensions of the carboxylated multi-walled carbon nanotubes are: an inner diameter of 2nm to 5nm, an outer diameter of 5nm to 15nm, and a length of 10μm to 30μm.

6. The method for preparing the cluster-derived rare earth-based composite electromagnetic wave absorbing material according to claim 1, characterized in that: The specific preparation process of the composite is as follows: Ultrasonic dispersion of carboxylated multi-walled carbon nanotubes in water to obtain a carboxylated multi-walled carbon nanotube solution; dispersing the cluster compound crystals in water by ultrasonication to obtain a cluster compound crystal solution; The carboxylated multi-walled carbon nanotube solution and the cluster compound crystal solution are mixed and then subjected to ultrasonic treatment. After the ultrasonic treatment is completed, the mixture is filtered and dried to obtain the composite.

7. The method for preparing the cluster-derived rare earth-based composite electromagnetic wave absorbing material according to claim 6, characterized in that: The ultrasonic treatment is continued for 8 h to 12 h.

8. The method for preparing the cluster-derived rare earth-based composite electromagnetic wave absorbing material according to claim 6, characterized in that: The temperature of the ultrasonic treatment was controlled at ≤ 60 °C.

9. The method for preparing the cluster-derived rare earth-based composite electromagnetic wave absorbing material according to claim 1, characterized in that: The calcination time is 2h.

10. A cluster-derived rare earth-based composite electromagnetic wave absorbing material prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Rare earth magnet and manufacturing method thereof

    CN101276665A

  • MOF-derived carbon-based magnetic nano composite electromagnetic wave absorbing material and preparation method thereof

    CN115491177A

  • Preparation method and application of carbon-based magnetic nano composite wave-absorbing material

    CN115633500A

  • Preparation method and application of carbon-based composite wave-absorbing material

    CN116285886A

  • Rare earth neodymium / transition metal ion double-substituted M-type barium ferrite wave-absorbing powder material and preparation method thereof

    CN117285341A